Development of rural areas and small cities through creative tourism: The CREATOUR project - Bakas, Fiona Eva (2018)
This research focuses on the CREATOUR project which investigates how organizations, tourists and communities in small cities and rural areas in Portugal interact and forge new alliances. CREATOUR is a three-year research and application project, involving five research centres, that started in 2016 and is creating a network of creative tourism offers in Portugal. Participants are 40 pilot projects, which are entrepreneurs or organizations who are incentivized to offer innovative creative tourism products within rural areas and small cities. Data that supports this article is based on articles written about the project by CREATOUR researchers and researchers’ participant observation accounts. This paper aims to: 1) provide an overview of this innovative research and application project, 2) present examples of creative tourism offers developed within the project and 3) to examine two development frameworks in wich creative tourism offers are placed in, in a non-urban context. The insights that this article presents, can be useful in practical and theoretical terms when other countries attempt to create similar creative tourism networks.